Analisis Wacana Kritis pada Pernyataan @DOKTERDETEKTIF tentang Penghentian Sementara Penjualan Skincare: Analisis Wacana Kritis pada Pernyataan @DOKTERDETEKTIF tentang Penghentian Sementara Penjualan Skincare - Sugiantoro, Hari Akbar; Pulungan, Jeni Anici; Annisa, Fhena (Borobudur Communication Review, 2025)
This study analyzes critical discourse in the TikTok account @DOKTERDETEKTIF statement regarding the temporary suspension of skincare sales through the video “Permintaan maaf dari Doktif”. The analysis was conducted using Teun A. Van Dijk's model, which includes the dimensions of text, social cognition, and social context. The results of the study show that the statement is not neutral but rather laden with communication strategies. In the textual dimension, the use of emotional strategies to build closeness with the audience, rational strategies by presenting scientific evidence and laboratory results, and defensive strategies to refute accusations and construct a narrative as a victim were identified. In the social cognition dimension, Doktif frames himself as an honest, credible, and wronged figure, while the opposing party is portrayed as manipulative. In the social context, Doktif position as both a doctor and an influencer grants him the power to control the narrative and influence public opinion. Thus, @DOKTERDETEKTIF statements are not merely clarifications but rather discursive strategies to maintain a positive image, build audience loyalty, and preserve symbolic power in the digital space.